QUANTITATIVE SEX-WISE OBSERVATION ON THE LENGTH-WEIGHT RELATIONSHIP OF THE BRAIN AND BODY IN A TELEOST, AMBLYPHARYNGODON CHAKIENSIS (BLEEKER) - SHERLY, P.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
The quantitative sex-wise observations were made for length-weight relationships like standard length-brain length (SL-BL) and standard length-brain weight (SL-BRW) relationship in Amblypharyngodon chakiensis, a teleost. Regression coefficient for SL-BL relationship in females is 0.1042 and that of males is 0.0303, while SL-BRW relationship in A. Chakiensis indicate that in females the regression coefficient is 0.4597 and in males it is 0.4078. Thus the rate of growth of brain length and brain weight is found to be higher in females.